Suppression of starch accumulation in 'sugar leaves' of rice affects plant productivity under field conditions. (2nd January 2017) - Okamura, Masaki; Hirose, Tatsuro; Hashida, Yoichi; Ohsugi, Ryu; Aoki, Naohiro
Abstract: While many plants accumulate the majority of their photoassmilates as starch during the daytime, some plants accumulate sucrose. Although the existence of these high-sucrose leaves, called 'sugar leaves', has long been known, the physiological characteristics of sugar leaves compared to 'starch leaves' remain unclear. In this study, the physiological roles of starch accumulation in rice, which has typical sugar leaves, were investigated using a mutant with suppressed leaf-starch biosynthesis. When grown under controlled conditions with light intensity of 400 μmol m −2 s −1, the initial growth of the mutant was similar to that of the wild-type plant, even with a 6-h-light/18-h-dark photoperiod in which carbon resources for growth are required during the night. This finding indicates that rice does not rely on leaf starch as a carbon resource during the night. By contrast, under field conditions, the grain yields of the mutant were significantly lower than those of the wild type only when the plants were exposed to full sunlight during the ripening period. These results may indicate that starch accumulation in sugar leaves plays an important role in maintaining a high source capacity under sufficient light conditions rather than as a carbon resource for the plant's growth at night.